Ergonomic design of diagnostic ultrasound transducers: Analysis, redesign/modeling, simulation/ assessment and product - Paschoarelli, Luis C. [UNESP]; Coury, Helenice G.; Oliveira, Ana B.; Silva, José C.P. [UNESP] (My University, 2016)
The development of new technology has resulted in more precise medical ultrasound diagnostics; however, the intensive use of poorly designed equipment has been closely linked to musculoskeletal problems among physicians working with ultrasound. This study presents procedures for the analysis, redesign, modeling and simulation/assessment of diagnostic ultrasound transducers. The assessment was performed in four phases: 1 - evaluation during simulated activity and analysis of movement (electrogoniometry) with two commercial transducers; 2 -redesign of the product, in which the aspects of concept product, detailed product and modeling of the mock-ups were considered; 3 - evaluation during simulated activity with one mock-up and with two commercially available transducers. 4 - project revision and the development new mock-ups and a subjective assessment (perception scale) of all tested equipment. The project revision resulted in two new mock-ups that required smaller range of motion (P ≤ 0.05), better load distribution and achieved better acceptability. Systematic methodology of ergonomic design can be used to develop safer and more comfortable products..
Keywords: Ergonomic design; Modeling; Redesign; Simulation; Usability